Between me, my younger self and the whole world: letters to one's younger self as epistolary genre - Alyeksyeyeva , Iryna (Current issues of Ukrainian linguistics: theory and practice, 2020)
The research treats letters to one’s younger (usually teen) self posted on the Internet as epistolary genre marked with peculiar linguistic and pragmatic features. Though the letters to one’s self imply intrapersonal communication, i.e. the sender is identical to the addressee, it is not how the sender perceives the situation, which is revealed by the use of pronouns (I for the sender and you for the younger self). However, these two may merge and then we appears to refer to the author’s younger and current selves. Another feature of the letters is roles assumed by the addressors. They may occur as a mentor to their rebellious and anxious younger self, which correlates with the purpose of the letter – giving advice. Alternatively, the authors may position themselves as omniscient fortune-tellers who step in in times of trouble to offer support to their teen self by telling what is there to come. Each of the two roles and purposes correlates with specific language means. The mentor role turns the letter into a lesson where the Imperative Mood prevails. The role of a fortune-teller transforms the letter into an autobiographical sketch told in a bizarre way: the author shifts past events into the future with the help of deictic markers (e.g., today, this) and tenses (e.g., future tenses or their synonyms such as constructions to be about to and to be going to). The letters to one’s younger self that contain an autobiographical component provide the researcher with an insight into the process of identity construction, since they show how one endows identity with continuity and bridge the divide between one’s teen and adult selves. In addition, the letters meant as advice deliver the culture specific idea of what ‘a good life’ is: they are written to guide their actual intended audience, i.e. Internet (teen) users, in modern society and inform them of true values and right choices.
Keywords: letter to one’s younger self, epistolary genre, communicative event, identity, narrative.